(untitled) - Chen, E. C. M. (Hoboken, N.J., 2004)
The Electron Capture Detector and the Study of Reactions with Thermal Electrons provides just such a timely review, as well as a thorough evaluation of the results attained thus far. In addition, this text: *Summarizes other methods for studying reactions of thermal electrons with molecules ; * Reviews electron affinities and thermodynamic and kinetic parameters of atoms, small molecules, and large organic molecules obtained using various techniques ; *Describes ECD applications in analytical chemistry, physical chemistry, and biochemistry ; *Provides an Appendix with electron affinities in tabular form.
Keywords: Gas chromatography,Electrons,Sắc ký gas,Điện tử; Capture